À prendre ou à laisser ? - Jeanne Guien (EchoGéo)
Urban foraging and dumpster-diving (also known as « freeganism ») in the streets are practices that create various interactions and exchanges with people passing by, working in shops or collecting waste. Through an autoethnographical approach, the author analyses six years of dumpster-diving in the streets of Paris, in order to study what those interactions (and, sometimes, those conflicts) disclose about the ambiguous status of waste, waste recovery and women’s body today.